The introduction of Islamic finance in Libya: Capturing the opportunities for SMEs development / Abdulaziz M. Abdulsaleh. - Abdulsaleh, Abdulaziz M. (Universiti Teknologi Mara Selangor, 2017)
In most countries, especially the developing ones, SMEs have a dynamic role as engines through which the growth objectives can be accomplished. This is very true in the case of Libya where the economy has been over-reliant on oil and gas as well as inefficient public sector. Unfortunately, SMEs in Libya are not playing their expected role as access to finance remains to be a formidable challenge. While banks remain the major external financier, if not the only one, many studies found that Libyans in general avoid dealing with conventional banks mainly due to religious beliefs. However, the recent introduction of Islamic banking and finance in the country could be a game changer. As such, this paper attempts to assess the opportunities for SMEs development in Libya following the recent introduction of Islamic finance. The study is exploratory; therefore the relevant literature is sourced and reviewed. The review shows that there is a strong demand for Islamic finance products from Libyan businesses including SMEs. Coupled with a strong enabling environment in which political stability and regulatory clarity are maintained Islamic finance is viable and has the ability to significantly contribute to the development of SMEs sector.